Effect of Garlic Extract on Liver Histopathology of BALB/c Mice with Nicotine Exposure (Universitas Negeri Semarang, 2022)
Nicotine affects liver in the presence of free radicals. One of the antioxidants is allicin which is the most abundant organosulfur in garlic. The objective of this study is to determine the effect of garlic extract as an antioxidant on the liver histopathological features of BALB/c mice exposed to nicotine. This is an experimental study with with post-test only control group design. The research subject were 24 male BALB/c mice. The K- group was the healthy control. The K+ group was exposed to inhaled nicotine of 10 mg/kgBW. Groups P1 and P2 were exposed to 10 mg/kgBW inhaled nicotine and were given garlic extract 300 mg/kgBW and 500 mg/kgBW. Treatment was given for 14 days. Data were analyzed by Kruskal-Wallis test and considered significant if the p value 0.05 with 95% confidence interval. Liver degeneration was grouped into normal, parenchymatous degeneration, hydropic degeneration, and necrosis. The results in the following groups: K: 80%, 20%, 0%, 0%; K(-) :0%,0%,87%,13% ; P1 : 0%,60%,40%,0%; P2 : 0%,100%,0%,0%. There was a significant difference in the degree of degeneration between groups (p=0.001). Garlic extract can reduce the degree of microscopic damage to the liver of BALB/c mice exposed to nicotine inhalation.